PENJAMINAN MUTU PERGURUAN TINGGI: DILEMA POLITIK ORGANISASI DAN URGENSI PENGGUNAAN PROFESIONAL EKSTERNAL - Suci, Afred (LPM IHDN Denpasar, 2017)
Higher education institutions (HEI) are encouraged to develop Internal Quality Assurance System (IQAS) that could assist the process of external audit, accreditation and to face the tight competition. General phenomenon of HEI’sIQAS,so far, is still away from qualified and even practically tends to be manipulative. This literature-based article aims to review the role of leadership in campus political practice and the urgence of external professional usage in order to improve internal quality assurance in HEI. The study reveals that improper campus political practice has become the bottleneck for the effectiveness of IQAS. It needs a fundamental change of top leader’s paradigm, particularly in the policy of internal auditor placement. A revolutionary breakthrough of hiring external professional tobe placed as internal auditor seems to be needed, specifically to keep the independency and objectivity, as well as to assure the qualified performance of all units in HEI.